2017
DOI: 10.5194/jsss-6-269-2017
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated optimizations of an electromagnetic acoustic transducer with artificial neural networks as metamodels

Abstract: Abstract. Electromagnetic acoustic transducers (EMATs) are noncontact transducers generating ultrasonic waves directly in the conductive sample. Despite the advantages, their transduction efficiencies are relatively low, so it is imperative to build accurate multiphysics models of EMATs and optimize the structural parameters accordingly, using a suitable optimization algorithm. The optimizing process often involves a large number of runs of the computationally expensive numerical models, so metamodels as subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Existing electromagnetic-acoustic diagnostic tools, due to the double mutual conversion of electromagnetic and acoustic waves, are significantly inferior in sensitivity and accuracy to acoustic tools with traditional contact piezoelectric transducers. A literature review revealed many publications of research results aimed at increasing the sensitivity and information content of the electromagnetic-acoustic monitoring method [12][13][14][15]. Of particular interest are research and development on non-contact testing of extended and large-sized metal structures by scanning them with acoustic waves generated by electromagnetic-acoustic transducers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Existing electromagnetic-acoustic diagnostic tools, due to the double mutual conversion of electromagnetic and acoustic waves, are significantly inferior in sensitivity and accuracy to acoustic tools with traditional contact piezoelectric transducers. A literature review revealed many publications of research results aimed at increasing the sensitivity and information content of the electromagnetic-acoustic monitoring method [12][13][14][15]. Of particular interest are research and development on non-contact testing of extended and large-sized metal structures by scanning them with acoustic waves generated by electromagnetic-acoustic transducers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Обратная задача -идентификация напряженно-деформированного состояния и уровня поврежденности структуры металла оборудования по значениям параметров гармонических составляющих сигнала ЭМАП может быть решена применением метода спектрального анализа». Но из-за большого объема исходной информации, которую необходимо при этом обработать, без использования современных интеллектуальных нейросетевых технологий это сделать практически невозможно, учитывая опыт подобных исследований, схожих по количеству обрабатываемых данных [7,8,12,[17][18][19][20].…”
unclassified